2011
DOI: 10.1111/j.1574-6968.2010.02191.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity and dietary association of rumen Treponema revealed using group-specific 16S rRNA gene-based analysis

Abstract: Treponema spp. are a commonly detected bacterial group in the rumen that are involved in the degradation of soluble fibers. In this study, a ruminal Treponema group-specific PCR primer targeting the 16S rRNA gene was designed and used to assess the phylogenetic diversity and diet association of this group in sheep rumen. Total DNA was extracted from rumen digesta of three sheep fed a diet based on alfalfa/orchardgrass hay or concentrate. The real-time PCR quantification indicated that the relative abundance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 47 publications
6
67
0
Order By: Relevance
“…It appeared that versatile Butyrivibrio species that can degrade several types of polysaccharides (hemicellulose, starch, and pectin) are abundant in the liquid fraction irrespective of the diets. The two OTUs assigned to Treponema are thought to be associated with diets rich in concentrate as described previously (Bekele et al 2011). "Unclassified_Bacteroidetes" (seven OTUs) and "Unclassified_Clostridiales" (six OTUs) were the first and second most abundant unclassified groups in the Lq-H sample, while "Unclassified_Lachnospiraceae" (eight OTUs) was the most abundant unclassified group in the Lq-C sample.…”
Section: Resultsmentioning
confidence: 95%
“…It appeared that versatile Butyrivibrio species that can degrade several types of polysaccharides (hemicellulose, starch, and pectin) are abundant in the liquid fraction irrespective of the diets. The two OTUs assigned to Treponema are thought to be associated with diets rich in concentrate as described previously (Bekele et al 2011). "Unclassified_Bacteroidetes" (seven OTUs) and "Unclassified_Clostridiales" (six OTUs) were the first and second most abundant unclassified groups in the Lq-H sample, while "Unclassified_Lachnospiraceae" (eight OTUs) was the most abundant unclassified group in the Lq-C sample.…”
Section: Resultsmentioning
confidence: 95%
“…were among the gut-associated genera that were more prevalent in indoor samples. Treponema has previously been associated with digital dermatitis in cattle (31) and in the bovine rumen (32). Phocaeicola and Paludibacter have also been positively associated with valerate in the rumen (33) and were more prevalent in outdoor samples.…”
Section: Discussionmentioning
confidence: 98%
“…Some Treponema species have been shown to interact with cellulolytic bacteria and increase the degradation rate of cellulose (56), and Treponema spp. also are involved in degradation of soluble fibers (57). Recent studies also have identified abundant Treponema in a termite gut metagenome (58) and enriched in the gut microbiomes of humans with highly fibrous hunter-gatherer diets (59).…”
Section: Discussionmentioning
confidence: 99%